How many ordered pairs of integers ( x , y ) are there such that
x ( x + 5 ) = ( y + 1 ) ( y + 2 ) ( y + 3 ) ( y + 4 ) ?
This section requires Javascript.
You are seeing this because something didn't load right. We suggest you, (a) try
refreshing the page, (b) enabling javascript if it is disabled on your browser and,
finally, (c)
loading the
non-javascript version of this page
. We're sorry about the hassle.
Nicely done!
Nice!
Awesome. Seriously, this should get a medal or something.
We let n = y + 1 and note that we can turn the RHS of the given equation into ( n 2 + 3 n + 1 ) 2 − 1 through the equality a ( a + 1 ) ( a + 2 ) ( a + 3 ) + 1 = ( a 2 + 3 a + 1 ) 2 . Thus, we are looking for x such that x ( x + 5 ) is 1 less than an odd square number (since n 2 + 3 n + 1 is always odd if n ∈ Z ).
Let m = n 2 + 3 n + 1 . Then x 2 + 5 x + 1 = m 2 . Since both x , m ∈ Z , m = x + k for some integer k . Thus, x 2 + 5 x + 1 = m 2 = ( x + k ) 2 = x 2 + 2 k x + k 2 → 5 x + 1 = 2 k x + k 2 . We then have x = 5 − 2 k k 2 − 1 , which we can turn into x = 4 1 ( − 2 k − 5 + 5 − 2 k 2 1 ) through polynomial long division. In order for x to be an integer, 5 − 2 k must divide 2 1 , which gives us that k = − 8 , − 1 , 1 , 2 , 3 , 4 , 6 , 1 3 . These values for k give x = 3 , 0 , 0 , 3 , − 8 , − 5 , − 5 , − 8 , respectively. Note that in each of these pairs ( x , k ) , x + k is odd, which means that ( x + k ) 2 = m 2 is odd, as desired.
Therefore, we have that x = − 8 , − 5 , 0 , 3 → x ( x + 5 ) = 2 4 , 0 , 0 , 2 4 . Thus, there are two values of x which make the LHS equal to 2 4 in the original equation and we can easily see that there are two values of y which make the RHS equal to 2 4 (these are y = − 5 , 0 ). There are also two values of x which make the LHS equal to 0 and four values of y which make the RHS equal to 0 (these are y = − 1 , − 2 , − 3 , − 4 ). We have verified above that no other value can be attained by the LHS and the RHS simultaneously, and thus, the final answer is 2 ⋅ 2 + 2 ⋅ 4 = 1 2 .
The trick with long division and 5 − 2 k dividing 2 1 is very nice, everyone should keep it in mind for future problems.
Useful trick: the product of 4 consecutive integers plus one is a perfect square.This follows from:
z ( z + 1 ) ( z + 2 ) ( z + 3 ) + 1 = ( z 2 + 3 z α ) ( z 2 + 3 z + 2 ) + 1 = α ( α + 2 ) + 1 = ( α + 1 ) 2
Hence, let's write x 2 + 5 x + 1 = z 2 . When x>3, we have:
x 2 + 4 x + 4 < x 2 + 5 x + 1 < x 2 + 6 x + 9
By symmetry of the parabola, when x<-8, we have x ( x + 5 ) + 1 = x ′ ( x ′ + 5 ) + 1 for x ′ = − 5 − x > 3 which redcues to the earlier case. Hence, we only need to consider x=-8, ..., 3. This gives:
Case 1 : x = -8, 3. Thus, x ( x + 5 ) = 2 4 and one easily sees that y=0, -5. This gives 4 solutions for (x,y).
Case 2 : x = 0, -5. Thus, x ( x + 5 ) = 0 and we get y=-1, -2, -3, -4. This gives 8 solutions for (x,y).
This "between two perfect squares" argument was used successfully in several solutions, it was actually the one we originally intended.
It took me a minute to figure out what your argument for x > 3 was saying. In case anyone else is wondering, he is saying that x > 3 → ( x + 2 ) 2 < x 2 + 5 x + 1 < ( x + 3 ) 2 , which is impossible since we can't have a square which is strictly between two consecutive squares.
Other than that, great argument. Very concise.
First, we observe that putting x=0 and x=-5, we can reduce the LHS into 0. So for each of x=0 and x=-5, we can reduce the RHS into 0 in 4 ways i.e. by making y = -1, -2, -3, -4. So we get 8 doubles.
Next, assuming that the RHS and LHS are both non-zero, we have the RHS as a product of 4 consecutive integers. A clever investigation reveals that the RHS is a multiple of 24 always. So, the LHS must also be a multiple of 24.
Hence, we write the equation as x(x+5) = 24m, where m is any integer. Clever investigations yield that if m = 1, then we get x(x+5) = 24 which is always true for x=3. So we get one more double.
Next, we try to find more such doubles. The discriminant is a perfect square, hence
25 + 96m = p^2 where p is an integer. We re-write this as (p+5)(p-5) = 96m.
Clearly if p+5=96 and p-5 = m OR p+5=m and p-5 = 96 we obtain two more doubles. But now let us observe the other values of p+5 and p-5.
Let, p+5 = k and p-5 = 96m/k. Subtracting, we have k - 96m/k = 10.
Now we come to the following conclusion: there must be some k for which the above holds, other than k = m or 96. We use the derivative rule to find that the derivative vanishes for k = 48. So, we have yet another pair.
The derivative rule restricts further pairs.
So answer is 12.
We can write R.H.S. as ( ( y + 1 ) ( y + 4 ) ) ( ( y + 2 ) ( y + 3 ) )
i.e. ( y 2 + 5 y + 4 ) ( y 2 + 5 y + 6 ) . Let y 2 + 5 y = z ∈ Z , so the given equation becomes x ( x + 5 ) = z 2 + 1 0 z + 2 4 ---- ( i ) .
Now since --- ( i ) is a quadratic in x having integer roots, so it's discriminant should be a perfect square i.e.
2 5 + 4 z 2 + 4 0 z + 9 6 = k 2 for some k ∈ Z +
⟹ 4 z 2 + 4 0 z + 1 2 1 = k 2 ------ ( i i )
Again, since --- ( i ) is also a quadratic in z having integer roots, so it's discriminant should be a perfect square i.e.
1 0 0 − 9 6 + 4 x 2 + 2 0 x = n 2 for some n ∈ Z +
⟹ 4 ( x 2 + 5 x ) + 4 = n 2
⟹ 4 ( z 2 + 1 0 z + 2 4 ) + 4 = n 2 ( U s i n g ( i ) )
⟹ 4 z 2 + 4 0 z + 1 0 0 = n 2 ------ ( i i i )
( i i ) - ( i i ) gives ,
2 1 = k 2 − n 2
⟹ 2 1 = ( k − n ) ( k + n )
Case I : k − n = 1 and k + n = 2 1 ⟹ k = 1 1 and n = 1 0 .So z = 0 , − 1 0 ⟹ y = 0 , − 5 ( R e j e c t i n g z = − 1 0 w h i c h g i v e s n o n − r e a l v a l u e s o f y ) and x = − 8 , 3 . These give a sub-total of 2 × 2 = 4 ordered pairs.
Case II : k − n = 3 and k + n = 7 ⟹ k = 5 and n = 2 . So z = − 6 , − 4 ⟹ y = − 1 , − 2 , − 3 , − 4 and x = 0 , − 5 giving a sub-total of 2 × 4 = 8 ordered pairs.
So the total number of ordered pairs of integer solutions is 4 + 8 = 1 2 .
Noticing the symmetry of the roots of the polynomials on each side about 5 / 2 inspires the following rearrangement
4 ( 2 x + 5 ) 2 − 1 0 0 = [ ( 2 y + 5 ) 2 − 9 ] [ ( 2 y + 5 ) 2 − 1 ]
and rearranging further
[ 2 ( 2 x + 5 ) ] 2 = [ ( 2 y + 5 ) 2 − 5 ] 2 + 8 4 .
Letting u = 2 ( 2 x + 5 ) and v = ( 2 y + 5 ) 2 − 5 we can find integers u , v satisfying u 2 − v 2 = ( u + v ) ( u − v ) = 8 4 by examining the different factorizations of 8 4 . So if 8 4 = a b then 2 x + 5 = ( a + b ) / 4 so we can ignore factorizations where a + b = 0 mod 4 . Thus we only need to consider 2 × 4 2 , 6 × 1 4 , − 2 × − 4 2 and − 1 4 × − 6 . Substituting these in allows us to see that the only possible ( x , y ) belong to the set { ( 3 , 0 ) , ( − 8 , 0 ) , ( 3 , − 5 ) , ( − 8 , − 5 ) , ( 0 , − 1 ) , ( 0 , − 2 ) , ( 0 , − 3 ) , ( 0 , − 4 ) , ( − 5 , − 1 ) , ( − 5 , − 2 ) , ( − 5 , − 3 ) , ( − 5 , − 4 ) } , a total of 1 2 solutions.
Add 1 to both sides and we get $$x^2 + 5x + 1 = (y^2 + 5y + 5)^2$$ For simplicity let t = y 2 + 5 y + 5 ∈ Z , then $$x^2 + 5x + 1 = t^2$$ 1) For x ≥ 3 we have $$(x + 2)^2 \leq x^2 + 5x + 1 = t^2 \leq (x + 3)^2$$ which is a contradiction, because perfect square can't be between two consecutive perfect squares.
2) For x ≤ 8 we have $$(x + 3)^2 \leq x^2 + 5x + 1 = t^2 \leq (x + 2)^2$$ which is a contradiction for the same reason. Hence it suffices to consider finitely many cases (which is very easy thanks to our first equation) $$x = -7,-6,\dots,2$$ to get only $$\boxed{12}$$ solutions.
There are a couple of misprints here, corrected in the comments. This "between two perfect squares" argument was used successfully in several solutions, it was actually the one we originally intended.
Let z = y 2 + 5 y + 5 then the equation becomes x 2 + 5 x = [ ( y + 1 ) ( y + 4 ) ] [ ( y + 2 ) ( y + 3 ) ] = ( z − 1 ) ( z + 1 ) = z 2 − 1 making a quadratic in terms of x we have: x 2 + 5 x − ( z 2 − 1 ) = 0 in order for x to be an integer discriminant of quadratic must be a perfect square: 4 z 2 + 2 1 = w 2 ( w − 2 z ) ( w + 2 z ) = ( 3 × 7 ) or ( − 3 × − 7 ) or ( 1 × 2 1 ) . . . which gives us z = ± 1 , 5 . if z = ± 1 then x = 0 , − 5 and y = − 1 , − 2 , − 3 , − 4
so 8 orderd pairs from here.if z = 5 then y = 0 , − 5 and x = 8 , − 3 so 4
orderd pair from here. total orderd pairs of ( x , y ) that satisfies the equation are 1 2 .
Both expressions in x and y are symmetric. Substitute x=(u-5)/2 and y=(v-5)/2. This gives 4 (u^2 - 25)=(v^2 -1)(v^2 -9).
Then rewrite into form: v^4 + b.v^2 + c. Now it follows: v^2=5 +/- sqrt (u^2 -21). Only solutions for u^2-21 being a perfect square are u^2 equal to 25 or 121. Proof: difference between to perfect squares is at least (n+1)^2 - n^2 = 2n+1 for any n. So u^2-k^2 > 21 for any k as soon as u> 11. The rest is just checking cases and rewriting u and v back to x and y.
Letting z = y 2 + 5 y + 5 , we have:
x 2 + 5 x = x ( x + 5 ) = ( y + 1 ) ( y + 2 ) ( y + 3 ) ( y + 4 ) = [ ( y + 1 ) ( y + 4 ) ] [ ( y + 2 ) ( y + 3 ) ] = ( y 2 + 5 y + 4 ) ( y 2 + 5 y + 6 ) = ( z − 1 ) ( z + 1 ) = z 2 − 1
So x 2 + 5 x + ( 1 − z 2 ) = 0 . Considering this as a quadratic equation in x , we have x = 2 − 5 ± 5 2 − 4 ( 1 − z 2 ) = 2 − 5 ± 2 1 + 4 z 2 . Since x is an integer, the discriminant is a square - so we can write d 2 = 2 1 + 4 z 2 , where we may take d to be non-negative. This means 2 1 = d 2 − 4 z 2 = ( d + 2 z ) ( d − 2 z ) . The only possible (unordered) pairs are { d − 2 z , d + 2 z } = { 1 , 2 1 } , { 3 , 7 } , { − 1 , − 2 1 } , { − 3 , − 7 } . We want ( d − 2 z ) + ( d + 2 z ) = 2 d to be non-negative, so we only take the first two pairs. So we either have: d = 1 1 and z = ± 5 , or d = 5 and z = ± 1 . For d = 5 , we can calculate x to be − 5 or 0 , so x ( x + 5 ) = 0 . Thus, in both cases, we have ( y + 1 ) ( y + 2 ) ( y + 3 ) ( y + 4 ) = 0 , so y = − 1 , − 2 , − 3 , − 4 are the only solutions. For d = 1 1 , we can calculate x to be 3 or − 8 , so x ( x + 5 ) = 2 4 . If z = 5 , we have 5 = y 2 + 5 y + 5 , so y ( y + 5 ) = 0 ⇒ y = 0 or − 5 . If z = − 5 , we have − 5 = y 2 + 5 y + 5 , so y 2 + 5 y + 1 0 = 0 . This has a negative discriminant, so there are no real solutions for y .
So all in all, the solutions for ( x , y ) are:
( − 5 , − 1 ) , ( − 5 , − 2 ) , ( − 5 , − 3 ) , ( − 5 , − 4 ) , ( 0 , − 1 ) , ( 0 , − 2 ) , ( 0 , − 3 ) , ( 0 , − 4 ) , ( 3 , 0 ) , ( 3 , − 5 ) , ( − 8 , 0 ) , ( − 8 , − 5 )
Our answer is thus 1 2 .
The equation above is equivalent with x 2 + 5 x = ( ( y + 2 5 ) 2 − 4 1 ) ( ( y + 2 5 ) 2 − 4 9 ) So that x 2 + 5 x = ( y + 2 5 ) 4 − 4 1 0 ( y + 2 5 ) 2 + 1 6 9 By multiplying the equation with 1 6 , we get that 1 6 x 2 + 8 0 x = ( 2 y + 5 ) 4 − 1 0 ( 2 y + 5 ) 2 + 9 Let ( 2 y + 5 ) 2 = k , then 1 6 x 2 + 8 0 x = k 2 − 1 0 k + 9 By completing the square, we get ( 4 x + 1 0 ) 2 − ( k − 5 ) 2 = 8 4 By factorizing, we get ( 4 x + k + 5 ) ( 4 x − k + 1 5 ) = 8 4 Consider that ( 4 x + k + 5 ) and ( 4 x − k + 1 5 ) is the factor of 8 4 . By checking all of possible values, we get 6 pairs ( x , k ) which their values are ( 0 , 1 ) ; ( 0 , 9 ) ; ( 3 , 2 5 ) ; ( − 5 , 1 ) ; ( − 5 , 9 ) ; ( − 8 , 2 5 ) . Substituting the value of k to equation ( 2 y + 5 ) 2 = k , we get 1 2 ordered pairs ( x , y ) . They are ( 0 , − 1 ) ; ( 0 , − 2 ) ; ( 0 , − 3 ) ; ( 0 , − 4 ) ; ( − 5 , − 1 ) ; ( − 5 , − 2 ) ; ( − 5 , − 3 ) ; ( − 5 , − 4 ) ; ( 3 , 0 ) ; ( 3 , − 5 ) ; ( − 8 , 0 ) ; ( − 8 , − 5 ) . So, the answer is 1 2 .
Since that 4 ( y + 1 ) ( y + 2 ) ( y + 3 ) ( y + 4 ) + 4 = 4 [ ( y + 1 ) ( y + 4 ) ] [ ( y + 2 ) ( y + 3 ) ] + 4 = 4 ( y 2 + 5 y + 5 − 1 ) ( y 2 + 5 y + 5 + 1 ) + 4 = 4 ( y 2 + 5 y + 5 ) 2 − 4 + 4 = [ 2 ( y 2 + 5 y + 5 ) ] 2 ,
4 x ( x + 5 ) + 4 is a perfect square, 4 x ( x + 5 ) + 4 = p 2 , p = 2 ∣ y 2 + 5 y + 5 ∣ ∈ N
Notice that p 2 = 4 x ( x + 5 ) + 4 = 4 x 2 + 2 0 x + 4 = ( 2 x + 5 ) 2 − 2 1 = M 2 − 2 1 , were M = 2 x + 5 , M is odd.
So we have M 2 − 2 1 = p 2 ⇒ ( ∗ ) ( M + p ) ( M − p ) = M 2 − p 2 = 2 1 = 7 ∗ 3 and since that p ∈ N , we have M + p ≥ M − p and by the ( ∗ ) we have four cases:
M + p = 2 1 , M − p = 1 , where M = 1 1 , x = 3
M + p = 7 , M − p = 3 , where M = 5 , x = 0
M + p = − 1 , M − p = − 2 1 , where M = − 1 1 , x = − 8
M + p = − 3 , M − p = − 7 , where M = − 5 , x = − 5
If x = 0 , − 5 , we have x ( x + 5 ) = 0 , where ( y + 1 ) ( y + 2 ) ( y + 3 ) ( y + 4 ) = 0 ⇒ y = − 1 , − 2 , − 3 , − 4 .
And we have 8 solutions ( x , y ) , x = 0 , − 5 , y = − 1 , − 2 , − 3 , − 4 .
If x = − 3 , 8 , we have 4 x ( x + 5 ) + 4 = 1 0 0 and p = 1 0 , where 2 ∣ y 2 + 5 y + 5 ∣ = ± 1 0 ⇒ y 2 + 5 y + 5 = ± 5 ⇒ y = − 5 , 0 .
So we have more 4 solutions: ( i , j ) , x = − 3 , 8 , y = − 5 , 0 , totalizing twelve solutions.
In the last line is ( x , y ) , no ( i , j ) .
Let s = x + 3 and z = y + 1
It then becomes ( s − 3 ) ( s + 2 ) = z ( z + 1 ) ( z + 2 ) ( z + 3 )
s 2 − s − 6 = ( z 2 + 3 z ) ( z 2 + 3 z + 2 )
If we let t = z 2 + 3 z + 1 , it then becomes s 2 − s − 6 = t 2 − 1
( s − 2 1 ) 2 − 4 2 5 = t 2 − 1
( s − 2 1 ) 2 − t 2 = 4 2 1
( 2 s − 1 ) 2 − ( 2 t ) 2 = 2 1
( 2 s − 2 t − 1 ) ( 2 t + 2 s − 1 ) = 2 1
{ x , y } ⊂ Z ⇒ { s , t } ⊂ Z
So we can say that 2 s − 2 t − 1 ∈ { − 2 1 , − 7 , − 3 , − 1 , 1 , 3 , 7 , 2 1 } whilst 2 t + 2 s − 1 is the corresponding factor of 2 1 .
Solving we get the set of solutions :
( s , t ) ∈ { ( 6 , 5 ) , ( 3 , 1 ) , ( 3 , − 1 ) , ( 6 , − 5 ) , ( − 5 , 5 ) , ( − 2 , 1 ) , ( 0 , − 1 ) , ( − 5 , − 5 ) }
Remembering t = z 2 + 3 z + 1 only t = − 5 gives no real solutions of z .
Possible solutions of ( x , y ) are therefore ( 3 , 0 ) , ( 3 , − 5 ) , ( 0 , − 1 ) , ( 0 , − 4 ) , ( 0 , − 2 ) , ( 0 , − 3 ) , ( − 8 , − 5 ) , ( − 8 , 0 ) , ( − 5 , − 1 ) , ( − 5 , − 4 ) , ( , − 3 , − 2 ) , ( − 3 , − 3 )
Therefore there are 12 ordered pairs of integers x and y that satisfy the given equation.
Case 1: x ( x + 5 ) = 0 . Then x ∈ { − 5 , 0 } , y ∈ { − 4 , − 3 , − 2 , − 1 } .
Case 2: x ( x + 5 ) = 0 .Group the factors ( y + 1 ) ( y + 4 ) = y 2 + 5 y + 4 and ( y + 2 ) ( y + 3 ) = y 2 + 5 y + 6 .Let z = y 2 + 5 y + 4 . So, x ( x + 5 ) = z ( z + 2 ) . Denote this product as N. We rule out the possibility that N is negative since that would only be possible if z = − 1 but then x ( x + 5 ) = − 1 .
So, N is positive, and can be written as a product of numbers which differ by 5, and by 2. These factors can be both positive, or both negative. If these are both positive, then one is greater than N and one is less than N . If 0 < z ≤ x then z ( z + 2 ) ≤ x ( x + 5 ) . If 0 < x ≤ z + 2 then z ( z + 2 ) ≥ ( x + 2 ) ( x + 4 ) = x 2 + 6 x + 8 > x ( x + 5 ) . So, the only possibility is that z = x + 1 and then x ( x + 5 ) = x 2 + 5 x = ( x + 1 ) ( x + 3 ) = x 2 + 4 x + 3 so x = 3 , N = 2 4 = 3 × 8 = 4 × 6 . If y 2 + 5 y + 4 = 4 then y = − 5 , 0 so ( x , y ) = ( 3 , − 5 ) or ( 3 , 0 ) .
The negative factorizations are symmetric, and they also come from N = 2 4 = ( − 8 ) ( − 3 ) = ( − 6 ) ( − 4 ) : ( x , y ) = ( − 8 , − 5 ) or ( − 8 , 0 ) .
First of all, there are some trivial solutions where one of the factors is zero, I hope I can give these without further explanation:
(0,-1) (0,-2) (0,-3) (0,-4) (-5,-1) (-5,-2) (-5,-3) (-5,-4)
For the non-trivial solutions, we can simplify the equality slightly:
x(x+5) = (y+1)(y+4) . (y+2)(y+3)
= z(z+2) where z=(y+1)(y+4)
Now, suppose there is some solution involving z = a (a > 0).
Then z = -(a+2) is also a solution:
z(z+2) = -(a+2)(-(a+2)+2)
= -(a+2)(-a)
= a(a+2)
and -(a+2) must be negative.
So every solution for which (z > 0) must have a corresponding solution for which (z < 0), and x is the same.
Similar logic shows that every solution for which (x > 0) has a corresponding solution for which (x < 0), and z is the same.
So, we can restrict our search to cases where (x > 0) and (z > 0). Because any such solution gives the following set of solutions:
(x, z) (-(x+5), z) (x, -(z+2)) (-(x+5), -(z+2))
Looking at the equality again:
x(x+5) = z(z+2) where x > 0, z > 0
We can write: z = x + h where h > 0 , giving:
x(x+5) = (x+h)(x+h+2)
5x = 2x + 2xh + h(h+2)
3x = 2xh + h(h+2)
(3-2h)x = h(h+2)
Since h and x are positive, (3 - 2h) must be positive too, meaning that (h = 1) is the only candidate solution.
Solving with h=1 gives x=3, z=4; and z=4 corresponds to y=0 or y=-5.
So we have exactly four non-trivial solutions:
(3, 0) (3, -5) (-8, 0) (-8, -5)
for a total of 12 solutions.
Problem Loading...
Note Loading...
Set Loading...
We have x ( x + 5 ) = ( y + 1 ) ( y + 2 ) ( y + 3 ) ( y + 4 ) x ( x + 5 ) = ( y + 1 ) ( y + 4 ) ( y + 2 ) ( y + 3 ) x ( x + 5 ) = ( y 2 + 5 y + 4 ) ( y 2 + 5 y + 6 ) Let z = y 2 + 5 y + 5 . Now, x ( x + 5 ) = ( z − 1 ) ( z + 1 ) = z 2 − 1 We complete the square for x : x 2 + 5 x + 1 = z 2 ( x + 2 5 ) 2 − 4 2 1 = z 2 ( 2 x + 5 ) 2 − ( 2 z ) 2 = 2 1 Now, we use difference of squares: ( 2 x + 5 + 2 z ) ( 2 x + 5 − 2 z ) = 2 1 Since 2 1 = 3 ⋅ 7 , 21 can be split four ways.
Case 1: 2 1 = − 2 1 ⋅ − 1
The sum of the factors is -22, and so 4 x + 1 0 = − 2 2 , and x = − 8 .
Case 2: 2 1 = − 7 ⋅ − 3
The sum of the factors is -10, and so 4 x + 1 0 = − 1 0 , and x = − 5 .
Case 3: 2 1 = 3 ⋅ 7
The sum of the factors is 10, and so 4 x + 1 0 = 1 0 , and x = 0 .
Case 4: 2 1 = 1 ⋅ 2 1
The sum of the factors is 22, and so 4 x + 1 0 = 2 2 , and x = 3 .
Therefore, we have x = − 8 , − 5 , 0 , 3 .
If x = − 8 or x = 3 , ( y + 1 ) ( y + 2 ) ( y + 3 ) ( y + 4 ) = 2 4 , and y = − 5 , 0 . If x = − 5 or x = 0 , ( y + 1 ) ( y + 2 ) ( y + 3 ) ( y + 4 ) = 0 , so y = − 4 , − 3 , − 2 , − 1 .
Overall, our answer is 2 + 2 + 4 + 4 = 1 2 .